Percepción del cliente externo de la calidad del servicio de la pequeña empresa Delcont Tecnology del distrito de Punchana, noviembre 2020 - Tangoa Sanchez, Casandra Nadir (2021)
The research entitled "Perception of the external client of the quality of the service of the company Delcont Tecnology of the District of Punchana, November 20120" aims to determine and analyze the perception of the external client of the quality of the service of the company Delcont Tecnology of the city of Iquitos, district of Punchana period November 2020, the research is descriptive level with a quantitative approach, non-experimental design of transectional cut; The population consisted of 40 main external clients of the company, to obtain the required information the survey with closed questions was used. The investigation determined that 50% of customers consider that the quality of service is excellent and 8% consider that the quality of customer service is poor.